2016
DOI: 10.15171/ps.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Antimicrobial Activities of Essential Oils of Different Cultivars of Lemongrass (Cymbopogon flexuosus)

Abstract: Background: Cymbopogon flexuosus popularly known as lemongrass provides a lemon scented essential oil which is widely used in flavour and fragrance, perfumery, food and pharmaceuticals. The aim of the present study was to assess antimicrobial activities of essential oils of three lemongrass cultivars viz., Pragati, Praman and Suvarna. Methods: Essential oils were isolated from one month old plants by hydrodistillation in mini Clevenger apparatus for 2 h. Antimicrobial activities were determined by agar well di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The determined value (≥0.01%) [43] corresponds to our observation for Gram-negative bacteria (41-97 µL/L). Similar to our results, Gupta et al also demonstrated that citral has a stronger antimicrobial activity than lemongrass essential oil [44]. Citral was up to 10 times more active against some Acinetobacter baumannii strains than lemongrass essential oil in the study of Adukwu et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…The determined value (≥0.01%) [43] corresponds to our observation for Gram-negative bacteria (41-97 µL/L). Similar to our results, Gupta et al also demonstrated that citral has a stronger antimicrobial activity than lemongrass essential oil [44]. Citral was up to 10 times more active against some Acinetobacter baumannii strains than lemongrass essential oil in the study of Adukwu et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…Although commonly used as a spice, especially in Asian cuisine, Cymbopogon representatives are also used as insect repellents (e.g., C. nardus (L.) Rendle) and soil conservatives, among others. Cymbopogon, as a therapeutic agent, has been used throughout human history for anti-inflammatory [10,11], antibacterial [12][13][14], antihelmintic [15], antiproliferative [16][17][18], antihyperlipidemic and antihyperglycemic [19] purposes. These properties are attributed mainly to the essential oils (EOs) that Cymbopogon species contain.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamon EO is effective against many Gram-positive and Gram-negative bacteria and it is also used in the food industry with considerable results [ 16 ]. The antibacterial activity of eucalyptus and lemongrass EOs was reported in numerous studies available in the literature [ 17 , 18 ]. On the other hand, less experimental evidence is available to demonstrate the antibacterial efficacy of verbena EO [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%